Pemberdayaan Masyarakat Melaui Seminar Stunting Sebagai Upaya Mempersiapkan Generasi Unggul - Mawati, Tiarah; Arifuqin, Muhammad Amirul; Achmad, Najwa Tsania; Mukarramah, Faizatul; Pratama, Aditya Putra; Oktavian, Andhika Dwi; Arum, Putri Nirmala; Rahmaniyah, Irfana; Fawaid, Satriya (Maliki Interdisciplinary Journal, 2025)
This article discusses community service carried out in Kedungkandang, Malang by carrying out a socialization seminar on stunting. This activity includes education to parents to always pay attention to children's intake and development periodically to prevent cases of stunting in children. The research method in this article is qualitative with a literature study approach by collecting readings about stunting. In addition, the researcher will reveal the phenomenon experienced by the parents there as a form of sample/small picture of the things experienced by parents and children there. By holding this socialization, it is hoped that parents in Kedungkandang can better understand things related to stunting, such as the characteristics, causative factors, impacts, and how to deal with stunting correctly and appropriately.